Psychosocial transformation of the deaf community through inclusive empowerment programs: A case study of the PERINTIS CSR Program at PT. Kilang Pertamina International RU VI Balongan - Milly Mildawati; Versanudin Hekmatyar; Ade Subarkah; Dede Kuswanda; Tukino Tukino; Eko Gunawan Wibisosno; Fachry Arsyad; Mohamad Zulkifli; Andromedo Cahyo Purnomo; ⁠Shafira Putri Kusuma P (Priviet Social Sciences Journal, 2025)
The deaf community in Indonesia continues to face psychosocial challenges that extend beyond communication barriers, including low self-esteem, limited social participation, and social stigma. While many Corporate Social Responsibility (CSR) initiatives focus on economic outcomes, little is known about their impact on psychosocial well-being. This study explores the psychosocial transformation experienced by members of the Deaf community through the PERINTIS Program, a CSR initiative of PT. Kilang Pertamina International RU VI Balongan, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews with the program participants, parents, and the implementation team. A three-stage thematic analysis (open, axial, and selective coding) was conducted. The findings indicate that prior to joining the program, the participants often showed signs of withdrawal, low confidence, and emotional instability. After engaging in barista training and mentoring within an inclusive community space, the participants reported increased confidence, stronger social relationships, improved emotional regulation, and greater motivation for the future. These changes were facilitated by a strengths-based, gradual empowerment process supported by mentors and an inclusive social environment. This study highlights the importance of integrating psychosocial dimensions into CSR initiatives, showing that empowerment goes beyond technical skill-building to include identity reconstruction and social recognition. The results contribute to disability studies, social work practice, and CSR policy and suggest that similar community-based models may foster more sustainable and inclusive empowerment.